The Utilization Of Sawdust Waste As A Media For Sculpture - Rantung, R (Journal of Educational Method and Technology, 2019)
Technology has penetrated into the community as a necessity for the sake of acceleration, while art is an inseparable part of the needs of every human being's life, both fine art and applied art. Technology and art cannot be separated at every step forward but the residual waste of technology can used into works of art without using technological aids. Some sculpture works made of wood, cement, fiberglass, metal (brass). This research will look at the extent to which sawdust can used as a medium for making sculptures. Sawdust waste is found in many furniture industries and stage home industries. With sawdust for creative people can used as material for art work.Â Keywords: Sawdust; Waste; Sculpture